The Political (In)Stability of Funded Pension Systems - Roel Beetsma; Oliwia Komada; Krzysztof Makarski; Joanna Tyrowicz (Center for Economic Studies and ifo Institute (CESifo), 2020)
We analyze the political stability of capital funded social security. In particular, using a stylized theoretical framework we study the mechanisms behind governments capturing pension assets in order to lower current taxes. This is followed by an analysis of the analogous mechanisms in a fully-edged overlapping generations model with intra-cohort heterogeneity. Funding is efficient in a Kaldor-Hicks sense. Individuals vote on capturing the accumulated pension assets and replacing the funded pension pillar with a pay-as-you-go scheme. We show that even if capturing assets reduces welfare in the long run, it always has sufficient political support from those alive at the moment of the vote.
Keywords: H55; D72; E17; E27; 330; funded pensions; asset capture; majority voting; welfare